2018
DOI: 10.1002/isd2.12054
|View full text |Cite
|
Sign up to set email alerts
|

Four steps to identify mechanisms of ICT4D: A critical realism‐based methodology

Abstract: Questions such as 'What is ICT?' and 'What is development?' are relatively wellanswered and well-documented in literature but work connecting the two has been limited. Existing ICT4D studies tend to be descriptive or prescriptive in nature, and hence the explanation of how and why ICT works in the contexts of developing countries needs further investigation. ICT cannot by itself lead to development: it has to be deployed by actors in a given social, political, cultural, and technical context, under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…To answer the research questions, the study adopts Thapa and Omland's (2018) critical realism‐based methodology. Our aim is to understand the three stratified layers of critical realism: the empirical, the actual and the real, and the interplay between the events, structures and mechanisms in the context of our study, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To answer the research questions, the study adopts Thapa and Omland's (2018) critical realism‐based methodology. Our aim is to understand the three stratified layers of critical realism: the empirical, the actual and the real, and the interplay between the events, structures and mechanisms in the context of our study, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Following the works of Information Systems (IS) scholars (eg, Bygstad et al, 2016; Thapa & Omland, 2018), we adopt the critical realist methodology as advocated by Thapa and Omland (2018) in order to identify mechanisms in a particular context (Danermark, Ekström, Jakobsen, & Karlsson, 2002; Easton, 2010). According to Thapa and Omland's (2018) critical realism methodology, there are four steps in the identification of mechanisms in the ICT4D which are: Description of events: This involves describing the events in the phenomenon understudy. Identification of entities and associations: This is concerned with dimensions, aspects and components under study such as persons, organizations and systems. Abduction (theoretical re‐description): This focuses on interpreting the data using theory. Retroduction: “ is a meta‐process the outcome of which is the identification of mechanisms that explain what caused the events to occur ” (Easton, 2010, p. 124). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, we have Danermark et al's (2002) six‐stage explanatory framework, although not developed from IS literature, which has been used by IS scholars (eg, Dobson, Jackson, & Gengatharen, 2013; Ononiwu, 2015; Vega & Chiasson, 2019). Wynn and Williams (2012) methodological framework as well as Thapa and Omland's (2018) four‐stage model also exist. Despite the relevancy of these models, we follow Dobson et al (2013) to adopt the Danermark et al's model as shown in Table 2, because of its power in answering our research questions.…”
Section: Brief Overview Of Critical Realismmentioning
confidence: 99%